Capture the feeling: Memory practices in between the emotional affordances of heritage sites and digital media. (June 2021) - Bareither, Christoph
This article develops the concept of emotional affordances, which is first used to describe the capacities of heritage sites to enable, prompt and restrict particular emotional experiences of their visitors. Secondly, the article asks how the emotional affordances of digital media, particularly those taking effect in digital photography and social media practices, allow visitors to mediate the emotional affordances of a particular heritage site. The argument builds on an ethnographic study of visitors' digital image practices at the 'Memorial to the Murdered Jews of Europe' in Berlin and it demonstrates how visitors 'capture the feeling' of the memorial through such practices while also reshaping the experiences the place affords.